Tennis : A History from American Amateurs to Global Professionals - Ruth, Greg, 1986- (Book collections on Project MUSE., 2021)
"The arrival of the Open era in 1968 was a watershed in the history of tennis--the year that marked its advent as a professionalized sport. Merging wide-angle history with individual stories of players and off-the-court figures, Greg Ruth charts tennis's evolution into the game we watch today. His vivid account moves from the cloistered world of nineteenth-century lawn tennis through the longtime amateur-professional divide and the battles over commercialization that raged from the 1920s until 1968. From there, Ruth details the post-1968 expansion of the game as it was transformed by bankable superstars, a popular women's tour, rival governing bodies, and sponsorship money. What emerges is a fascinating history of the economics and politics that made tennis a decisive, if unlikely, force in the creation of modern-day sports entertainment. Comprehensive and engaging, this book tells the interlocking stories of the figures and factors that birthed the professional game"--